R&D planning at ARCO Chemical - Braunstein, David M.
David M. Braunstein and Miren C. Salsamendi relate the lessons ARCO has learned from revamping its planning process.
A new planning process helps R&D align its goals with the corporation's business strategy.
Corporations today must balance the support of current business needs with planning for future growth. The integration of the R&D objectives with that of the corporation is key to conquering this challenge. The alignment of the R&D strategy with the corporate strategy can take many approaches. The overriding principle, though, is the development of corporate mission and strategy statements by interactive consensus among the various departments. Given this interactively developed strategy, R&D can define and redefine its portfolio toward meeting the corporate objectives. Clear choices can and must be made if the process is to be successful.
Keywords: R&D planning